2019
DOI: 10.1590/1518-8345.2818.3192
|View full text |Cite
|
Sign up to set email alerts
|

Burnout syndrome in Brazilian and Spanish nursing workers

Abstract: Objective:to analyze the burnout dimensions scores in Brazilian and Spanish nursing workers.Method:quantitative, cross-sectional and comparative study conducted with 589 Nursing workers who answered the Sociodemographic and Professional Characterization Questionnaire and the Maslach Burnout Inventory. Descriptive and analytical analysis of the data was performed.Results:Spanish Nursing workers presented higher averages in the Depersonalization dimension (p = 0.004) and Brazilians, higher scores in the Professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 29 publications
4
12
0
9
Order By: Relevance
“…The MBI-HSS has shown good internal consistency in studies carried out in several countries such as Spain, Mexico, Chile, Portugal, Colombia and Brazil, ranging from 0.79 to 0.91 for the emotional exhaustion dimension (α=0.90 in the original version); between 0.69 and 0.87 for personal fulfillment (α=0.71 in the original version) and between 0.42 and 0.66 for the depersonalization dimension (α=0.79 in the original version). This lower score for the depersonalization dimension has, frequently, occurred in studies conducted outside the United States (1)(2)(3)(4)(9)(10) .…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The MBI-HSS has shown good internal consistency in studies carried out in several countries such as Spain, Mexico, Chile, Portugal, Colombia and Brazil, ranging from 0.79 to 0.91 for the emotional exhaustion dimension (α=0.90 in the original version); between 0.69 and 0.87 for personal fulfillment (α=0.71 in the original version) and between 0.42 and 0.66 for the depersonalization dimension (α=0.79 in the original version). This lower score for the depersonalization dimension has, frequently, occurred in studies conducted outside the United States (1)(2)(3)(4)(9)(10) .…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, it is relevant to develop analyses that prove that the items on a scale measure exactly what they propose. This is a psychological syndrome that develops in response to chronic interpersonal stressors in the workplace (1)(2)(3) . It is characterized by emotional exhaustion (feelings of extreme tiredness related to excessive physical and emotional effort); depersonalization (negative attitudes in interpersonal relationships, marked by cynicism and disinterest) and low personal fulfillment (negative self-assessment of oneself, work ability, and to deal with other people) (1,(4)(5)(6)(7) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, by analyzing all authors to build this study it was observed that the main triggering factors of burnout are high workload and the limited number of employees, factors that that lead to emotional exhaustion or physical these professionals. [5][6][7]10,11 Burnout syndrome is considered for many years as an important subject of research due to its high rate of incidence / prevalence and being assessed an occupational hazard. Several studies highlight the high risk of developing this syndrome among health professionals, especially among the nursing staff.…”
Section: Resultsmentioning
confidence: 99%
“…El estudio presentó como objetivo evaluar el síndrome de burnout en personal de salud asistencial en bases de datos que contengan literatura científica en América Latina entre 2015 -2020, en ese sentido se detallaron los principales hallazgos obtenidos, de acuerdo a la sistematización de los resultados, en cuanto al análisis de procedencia de los artículos se ha observado que esta es predominante de Brasil (14 artículos) seguido de Perú con 8 artículos, en las que se observan una brecha significativa con los demás países latinos, guarda relación con lo planteado por Miguel (2011) quien manifiesta que la producción científica en América Latina se encuentra distribuida de manera desigual, esto también se evidencia en la distribución de artículos obtenidos por Díaz et al (2016), donde efectúa una evaluación con estudios del síndrome de burnout que resulta una prevalencia mayor de países como Colombia, México y Brasil; sin embargo la muestra de estudio pese a tener como participantes a distintos trabajadores de la salud como el caso de médicos, enfermeras, auxiliares de enfermería entre otros, que guardan relación con el estudio actual planteado, también ha considerado otro grupo de profesionales, por cuanto estos tienden a atender de manera directa a un usuario, cliente, beneficiario como lo son los abogados, asistentes sociales, trabajadores sociales, familiares que se encargan del cuidado de enfermos, operadores telefónicos entre otros. En tanto el estudio presentado por Tabares-Díaz (2020) clasifica como primer lugar la producción brasilera con 31 artículos; es así que se considera que en los últimos años se ha presentado un mayor auge los cuales comprenden del 2012 al 2018 como manifiesta Mugnani (2018), así también menciona que fue debido a la necesidad de evaluación de salud mental solicitada en gran medida; de igual manera el estudio de burnout se efectúa a consecuencia de que los trastornos mentales como tal en las últimas décadas destacan un grave problema en el campo ocupacional y los servicios médicos (Baldonedo-Mosteiro et al, 2019).…”
Section: Discussionunclassified